Bioelectricity production in an indoor plant-microbial biotechnological system with Alisma plantago-aquatica - Rusyn, Iryna B.; Hamkalo, Кhrystyna R. (Acta Biologica Szegediensis, 2019)
The paper descibes the development of a biotechnological system for generating bioelectricity on closed balconies of buildings from living plants Alisma plantago-aquatica and soil microorganisms grown in containers with natural wetland substrate, provided with a graphite and Zn-galvanized steel electrode system. This biotechnology worked efficiently from the first days after installation and was practically at full capacity 2 weeks later. Electric power output was highest in the spring-summer and the early autumn period (at the time of the highest photosynthetic activity of plants). The highest current output was 58.6 mA at 10 Ω load. Bioelectricity generation by the biosystem was stable with slight fluctuations throughout the year in well-lighted and heated premises at a temperature of 21-26 °C, and the seasonal reduction of the bioelectricity level was 8.71%. On not-heated closed terraces and glazed balconies, with temperature fluctuations from 5 to 26 °C, the electricity production decreased in the winter period by 19.98% and 39.91% with and without adding of sulfate-reducing bacteria, respectively. The proposed system of electrodes for collection of bioelectric power is new, easy to manufacture and economical. It is resistant to waterlogged environment, and has good prospects for further improvements for more effective collection of plant-microbial bioelectricity. Maintainance of the biosystem is simple and accessible to everyone without special skills.